Hierarchical establishment of information sources during foraging decision-making process involving Acromyrmex subterraneus (Forel, 1893) (Hymenoptera, Formicidae) - De Almeida, Nilhian Gonsalves; Camargo, Roberto Da Silva [UNESP]; Forti, Luis Carlos [UNESP]; Santos Lopes, Juliane Floriano (Soc Brasileira Entomologia, 2018)
During foraging, worker ants are known for making use of many information sources to guide themselves in external environments, especially individual (memory) and social (trail pheromone) information. Both kinds of information act in a synergic way, keeping the foraging process efficient and organized. However, when social and individual information is conflicting face a trail bifurcation, it is necessary to establish a hierarchical order so prioritizing one of them. This study aims to verify which information (social or individual) is prioritized by Acromyrmex subterraneus workers when facing a bifurcation in a Y-trail system. Only one branch of the Y-trail leads to food resource and it had a section covered by filter paper where trail pheromone was deposited by workers. Pheromone deposition was here estimated by worker flow. After an individually marked forager (target-worker) made 1, 3 or 5 trips to the food resource, the filter paper was transferred to the branch which did not lead to the food. The time spent by target workers on branch selection and their right choice (branch with food) frequency were registered. Regardless of the target worker's previous trips to the resource, right choice frequency stood over 70%. In addition, the number of previous trips did not influence the time spent on decision making. However, the higher the flow of workers, the longer the time spent on decision making. By simulating a situation with conflicting information, it was possible to verify that a hierarchical order is established by A. subterraneus, which prioritized individual information (memory). (C) 2017 Sociedade Brasileira de Entomologia. Published by Elsevier Editora Ltda. This is an open access article under the CC BY-NC-ND license.
Keywords: Leafcutter ants; Trail pheromone; Memory; Synergism